Case Report: Mastocytosis: The Long Road to Diagnosis - Rama, Tiago Azenha; Martins, Diana; Gomes, Nuno; Pinheiro, Jorge; Nogueira, Ana; Delgado, Luís; Plácido, José Luís; Coimbra, Alice (Frontiers in Immunology, 2021)
Mastocytosis is a heterogeneous group of disorders characterized by expansion and accumulation of clonal mast cells. Patients mainly present with either cutaneous lesions, anaphylaxis, or both. Its low prevalence and unusual features often hinder its diagnosis for several years. We report the case of an 18-year-old male who was referred to our department with a long-standing history of atypical skin lesions, allergic rhinitis, exercise-induced bronchoconstriction and what was believed to be food-related flushing and anaphylaxis, that was later diagnosed with mastocytosis. This case illustrates the need to consider investigating for mastocytosis when recurrent anaphylaxis is present, especially in the presence of atypical skin lesions, even if normal serum basal tryptase levels and allergic sensitization are present.